Information theory and pattern recognition - Daemi, M.F. (1990)
This thesis presents an account of an investigation into the use of information theory measures in pattern recognition problems. The objectives were firstly to determine the information content of the set of representations of an input image which are found at the output of an array of sensors; secondly to assess the information which may be used to allocate different patterns to appropriate classes in order to provide a means of recognition; and thirdly to assess the recognition capability of pattern recognition systems and their efficiency of utilization of information. Information assessment techniques were developed using fundamental principles of information theory. These techniques were used to assess the information associated with attributes such as orientation and location, of a variety of input images. The techniques were extended to permit the assessment of recognition capability and to provide a measure of the efficiency with which pattern recognition systems use the information available.